Evaluating the Due Process and Crime Control Perspectives Using Rasch Measurement Analysis - Vanessa A. Edkins; Kenneth D. Royal (The Evaluation Center at Western Michigan University, 2011)
Background:  The biases jurors possess may influence everything from the interpretation of case evidence to impressions of the defendant to, ultimately, verdict and recognition of this has led to a number of juror attitude scales attempting to tap into important biases.  A common ideology discussed in legal research is that individuals attitudes toward the law and the legal system differ along a continuum moving from due process (a concern for the preservation of individual rights) to crime control (a focus on swift and harsh punishment for those who break the law) although an agreed upon assessment of these perspectives has yet to be created.  Purpose:  The current research addresses due process and crime control perspectives and uses the ideology as a source for a new measure of juror bias: The General Attitudes toward the Legal System (GALS) scale. Setting:  Not applicable. Intervention:  Not applicable. Research Design: The GALS scale was constructed based on existing theory and administered to nearly 700 undergraduate psychology students at a large Midwestern university. The psychometric properties of the instrument were then evaluated to determine instrument quality.  Data Collection and Analysis:  The Rasch Rating Scale Model (RRSM) was used to evaluate the psychometric properties of the GALS. Evaluation focused on six characteristics of the instrument: dimensionality, reliability, rating scale quality, item quality, item hierarchy, and measure quality. Findings:  Results indicate the GALS is a psychometrically sound instrument for measuring juror bias. Keywords: juror decision making; juror bias; scale development; instrument validation; psychometric evaluation